2010
DOI: 10.1128/cvi.00332-10
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Detection of IgM and IgG Class Antibodies toToxoplasma gondii, Rubella Virus, and Cytomegalovirus Using a Novel Multiplex Flow Immunoassay

Abstract: The goal of this study was to evaluate the BioPlex 2200 Toxoplasma, rubella, and cytomegalovirus (CMV) Congenital infections caused by Toxoplasma gondii, rubella, and cytomegalovirus (CMV) are a significant cause of neonatal mortality and childhood morbidity worldwide (6,18,21). Due to their nonspecific clinical manifestations and the importance of early recognition of in utero infection, serologic screening for these pathogens has been considered a routine practice in many parts of the world (11). Conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 21 publications
1
46
0
3
Order By: Relevance
“…Although our results should be considered estimates due to the limitation that only 10% of the BIFA-negative/ EIA-negative serum samples were tested by ELFA and CIA, they support previously published data from CMV IgM method comparison studies (15,(17)(18)(19)(20)(21). The pairwise concordance rates between EIA, ELFA, and CIA were all Ͼ90%; in contrast, the concordance rates of these 3 assays with BIFA were lower (84% to 86%), due in large part to sera that were positive by BIFA but not by the other three assays.…”
Section: Discussionsupporting
confidence: 77%
“…Although our results should be considered estimates due to the limitation that only 10% of the BIFA-negative/ EIA-negative serum samples were tested by ELFA and CIA, they support previously published data from CMV IgM method comparison studies (15,(17)(18)(19)(20)(21). The pairwise concordance rates between EIA, ELFA, and CIA were all Ͼ90%; in contrast, the concordance rates of these 3 assays with BIFA were lower (84% to 86%), due in large part to sera that were positive by BIFA but not by the other three assays.…”
Section: Discussionsupporting
confidence: 77%
“…This analyzer can detect different antibodies in a single tube, thus yielding highthroughput multiplexing analysis, saving time and preventing errors of result transmission. To our knowledge, only one study assessed the ToRC IgG and IgM immunoassays for toxoplasmosis serodiagnosis (6). In that study, the BioPlex 2200 ToRC IgG assays demonstrated a high agreement of 98.7% (592/600 specimens) with the routine practice used by the authors, while the ToRC IgM assays yielded an agreement of 91.2% (547/600 specimens).…”
Section: Discussionmentioning
confidence: 94%
“…The BioPlex 2200 ToRC IgG and IgM immunoassays already met these criteria in a prospective study on 600 serum samples subjected to routine testing (6). In another study, elevated sensitivity of IgM antibodies produced by recent infections was demonstrated (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All available panel 3 samples that were negative or equivocal for CMV IgG by the Wampole assay were tested for CMV IgG using an FDA-cleared chemiluminescent immunoassay (CIA) (Immulite, Siemens Diagnostics, Los Angeles, CA) (20). In all panel 2 samples and in CMV IgG-positive panel 3 samples, CMV IgM was measured with an FDA-cleared magnetic bead-based flow cytometric immunofluorescent assay (21), performed per the manufacturer's instructions (BioPlex 2200; Bio-Rad Laboratories, Hercules, CA). For this study, equivocal CMV IgM results were considered positive.…”
Section: Methodsmentioning
confidence: 99%